A Practical Approach to Incorporating ESG Risk Into Equity Valuation (Journal of Applied Business and Economics, 2024)
The rise in the capital allocated and investor focus attributed to ESG investing over the past several years has been significant. However, the current literature is not settled regarding the value that ESG risk measures and reporting has on investments and valuations. If this risk is essential, then this risk should be incorporated to account for the presence or the lack of ESG-related risk in valuation models. However, with the relative newness and difficulty of quantifying ESG risk, there is little practical guidance on incorporating this risk into valuation estimates. We provide evidence that ESG-related risk scores are positively associated with the cost of equity. Building upon that result, we operationalize the positive relationship to adjust the cost of equity in free cash flow to equity valuation models. Firms with higher ESG risk have a higher required return, while firms with lower ESG risk have a lower discount rate. Our approach is a practical guide for investors and analysts to account for ESG risk adjustments in valuation models.
Keywords: business; economics; ESG; equity analysis; equity valuation; free cash flow to equity; valuation methods